Thalidomide and pentoxifylline block the renal effects of supernatants of macrophages activated with Crotalus durissus cascavella venom - Martins,A.M.C. (2004)
Because thalidomide and pentoxifylline inhibit the synthesis and release of tumor necrosis factor-alpha (TNF-alpha), we determined the effect of these drugs on the renal damage induced by supernatants of macrophages activated with Crotalus durissus cascavella venom in order to identify the role of TNF-alpha in the process. Rat peritoneal macrophages were collected with RPMI medium and stimulated in vitro with C.d. cascavella venom (10 µg/ml) in the absence and presence of thalidomide (15 µM) or pentoxifylline (500 µM) for 1 h and washed and kept in culture for 2 h. Supernatant (1 ml) was tested on an isolated perfused rat kidney (N = 6 for each group). The first 30 min of each experiment were used as control. The supernatant was added to the perfusion system. All experiments lasted 120 min. The toxic effect of the preparation of venom-stimulated macrophages on renal parameters was determined. At 120 min, thalidomide (Thalid) and pentoxifylline (Ptx) inhibited (P < 0.05) the increase in perfusion pressure caused by the venom (control = 114.0 ± 1.3; venom = 137.1 ± 1.5; Thalid = 121.0 ± 2.5; Ptx = 121.4 ± 4.0 mmHg), renal vascular resistance (control = 4.5 ± 0.2; venom = 7.3 ± 0.6; Thalid = 4.5 ± 0.9; Ptx = 4.8 ± 0.6 mmHg/ml g-1 min-1), urinary flow (control = 0.23 ± 0.001; venom = 0.44 ± 0.01; Thalid = 0.22 ± 0.007; Ptx = 0.21 ± 0.009 ml g-1 min-1), glomerular filtration rate (control = 0.72 ± 0.06; venom = 1.91 ± 0.11; Thalid = 0.75 ± 0.04; Ptx = 0.77 ± 0.05 ml g-1 min-1) and the decrease in percent tubular sodium transport (control = 77.0 ± 0.9; venom = 73.9 ± 0.66; Thalid = 76.6 ± 1.1; Ptx = 81.8 ± 2.0%), percent tubular chloride transport (control = 77.1 ± 1.2; venom = 71.4 ± 1.1; Thalid = 77.6 ± 1.7; Ptx = 76.8 ± 1.2%), and percent tubular potassium transport (control = 72.7 ± 1.1; venom = 63.0 ± 1.1; Thalid = 72.6 ± 1.0; Ptx = 74.8 ± 1.0%), 30 min before and during the stimulation of macrophages with C.d. cascavella venom. These data suggest the participation of TNF-alpha in the renal effects induced by supernatant of macrophages activated with C.d. cascavella venom.